Lviv university during the first world war (1914 - 1918) - Olesia Isayuk (Cхід, 2013)
There are researched relations between Lviv university and military authorities in Lviv during the First world war. There are three relations models analyzed: University and Russian, Austrain and Polish military command. The main problems of these relations were requisitions of University buildings for military targets and continuous mobilizations, which deprived University from professors and technical workers. Thanks to these fact, University administration was forced to cooperate with military command for own inrterests defense. This article reviews pecularities of relations with each mentioned army.